Impact of ionomers on porous Fe-N-C catalysts for alkaline oxygen reduction in gas diffusion electrodes - Jinjie Zhu; Angus Pedersen; Simon Kellner; Robert D. Hunter; Jesús Barrio (Communications Chemistry)
Abstract Alkaline exchange membrane fuel cells (AEMFCs) offer a promising alternative to the traditional fossil fuel due to their ability to use inexpensive platinum group metal (PGM)-free catalysts, which could potentially replace Platinum-based catalysts. Iron coordinated in nitrogen-doped carbon (Fe-N-C) single atom electrocatalysts offer the best Pt-free ORR activities. However, most research focuses on material development in alkaline conditions, with limited attention on catalyst layer fabrication. Here, we demonstrate how the oxygen reduction reaction (ORR) performance of a porous Fe-N-C catalyst is affected by the choice of three different commercial ionomers and the ionomer-to-catalyst ratio (I/C). A Mg-templated Fe-N-C is employed as a catalyst owing to the electrochemical accessibility of the Fe sites, and the impact of ionomer properties and coverage were studied and correlated with the electrochemical performance in a gas-diffusion electrode (GDE). The catalyst layer with Nafion at I/C = 2.8 displayed the best activity at high current densities (0.737 ± 0.01 VRHE iR-free at 1 A cm⁻²) owing to a more homogeneous catalyst layer, while Sustainion displayed a higher performance in the kinetic region at the same I/C. These findings provide insights into the impact of catalyst layer optimization to achieve optimal performance in Fe-N-C based AEMFCs.